SINTESIS NANOSELULOSA DARI SERAT NANAS DAN APLIKASINYA SEBAGAINANOFILLERPADA FILM BERBASIS POLIVINIL ALKOHOL - Evi Savitri Iriani; Kendri Wahyuningsih; Titi Candra Sunarti; Asep Wawan Permana (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2015)
A variety of attempts have been made to reduce the dependence on petroleum raw materials based plastics which are limited supply the mechanical properties close to conventional plastic. The objectives of research was to know the effect of pineapple nanocellulose effective in increasing tensile strength and elongation, but the higher addition (of up to 50%) resulted in decreased elongation. The addition and without glycerol